Metal hydroxide based asymmetric supercapacitors - Chai, Guo Dong (2016)
As technology continues to improve, the potential of supercapacitor gets larger in the market. The reason for its emergence is due to its higher surface area electrodes and the material used to achieve greater capacitances and power densities. The unique charge storage from this device brings attention to researchers and many are trying to find the optimal electrode materials so as to bridge the gap between conventional capacitors and batteries.